Capacity for Empathy and Emotional Contagion in Those With Psychopathic Personalities - Cherie Luckhurst; Elaine Hatfield; Claire Gelvin-Smith (Interpersona: An International Journal on Personal Relationships, 2017)
People with psychopathic traits are sometimes adept at recognizing the emotions of others and using this knowledge in anti-social ways. However, data from incarcerated psychopaths suggest that they are incapable of true empathy. In this paper, we describe three studies that link psychopathic personality to emotional contagion and empathy, and we offer suggestions for reconciling the seemingly conflicting data. While most studies of psychopathic personality assess incarcerated respondents, the resulting data may not be generalizable to non-criminals; participants in these studies were recruited from the general population. The research confirms that empathy and emotional contagion are positively correlated and that each is negatively correlated with psychopathy, as expected. Unique to these studies is the finding that, when instructed, those with psychopathic traits can easily “catch” the emotions of others via the steps of the emotional contagion pathway, thus implying their capacity for empathy. However, without instruction, those with psychopathic traits did not automatically catch others’ emotions.